(untitled) (Journal of Humanities and Social Sciences Research, 2023)
The research aims to study the style of wishing with its original tool (night) in the poetry of the Umayyad spinning poet Omar bin Abi Rabia Al-Makhzoumi. Neilh, and the style of wishing is one of the methods of requesting construction that deviates from its original meaning to other meanings, but the rhetoricians did not speak of stating (I wish) a meaning other than wishing because of the antiquity of this tool in the wishing style, which is a sober Arabic style that the Arabic language gifted to its speaker so that he could express through it For his verbal purposes, we presented in this research the poetic evidence that contained the tool (night) in the poetry of Omar bin Abi Rabia and dealt with it in analysis and detail. And other cases when waiting for the wish to occur, through which these feelings and poetic experiences are reflected on the recipient, and he is affected and attracted towards the experience of the poet expressed. Keywords: